The stuff that dreams are made of: HIV‐positive adolescents' aspirations for development. (27th February 2018) - Hodes, Rebecca; Doubt, Jenny; Toska, Elona; Vale, Beth; Zungu, Nompumelelo; Cluver, Lucie
Abstract: Background: The Sustainable Development Goals (SDGs) commit to strengthening collaborations between governments and civil society. Adolescents are among the key target populations for global development initiatives, but research studies and programmes rarely include their direct perspectives on how to promote health and wellbeing. This article explores how both the methods and the findings of participatory research provide insights into adolescents' aspirations across the domains of health and social development. It investigates how adolescents conceive of health and social services as interconnected, and how this reflects the multisectoral objectives of the SDGs. Methods: This research was conducted within a longitudinal, mixed‐methods study of HIV‐positive adolescents (n = 80 qualitative participants, n = 1060 quantitative interviews). Between November 2013 and February 2014, a participatory exercise – the "dream clinic" – was piloted with 25 adolescents in South Africa's Eastern Cape. Key themes were identified based on the insights shared by participants, and through visual and thematic analysis. These findings were explored through a second participatory exercise, "Yummy or crummy? You are the Mzantsi Wakho masterchef !, " conducted in January 2016. Findings are described in relation to emerging quantitative results. Results: Mixed methods explored associations between access to food, medicines, clean water and sanitation in HIV‐positive adolescents' aspirations for development. The exercises produced practicable recommendations for innovations in development, based on associations between healthcare, food security, clean water and sanitation, while illustrating the value of partnership and collaboration (the objective of SDG17). Findings capture strong interlinkages between SDGs 2, 3 and 6 – confirming the importance of specific SDGs for HIV‐positive adolescents. Study results informed the objectives of South Africa's National and Adolescent and Youth Health Policy (2017). Conclusions: Participatory research may be used to leverage the perspectives and experiences of adolescents. The methods described here provide potential for co‐design and implementation of developmental initiatives to fulfil the ambitious mandate of the SDGs. They may also create new opportunities to strengthen the engagement of adolescents in policy and programming.